L5 Pre-clinical evaluation of aav5-mihtt gene therapy of huntington's disease in rodents. (13th September 2016) - Miniarikova, Jana; Zanella, Ilaria; Blits, Bas; Evers, Melvin; Zimmer, Virginie; Spoerl, Alexia; Southwell, Amber; Hayden, Michael; Deventer, Sander van; Deglon, Nicole; Petry, Harald; Konstantinova, Pavlina
Abstract : The most upstream therapeutic target in Huntington's disease (HD) is the mutated huntingtin (mtHTT) and gene silencing with artificial miRNAs (miHTTs) delivered by adeno-associated viral vector (AAV) is expected to have therapeutic benefit. We have taken two approaches for the development of RNAi-based gene therapy of HD: total HTT silencing by targeting exon 1 and allele-specific inhibition by targeting heterozygous SNPs or a deletion linked to mtHTT. Anti-HTT target sequences were incorporated in different pri-miRNA scaffolds and their knockdown efficacy, allele selectivity and pri-miHTT processing were analysed in vitro . The best miHTT candidates were incorporated in AAV5 vector and produced using the established uniQure baculovirus-based manufacturing platform. Proof of concept studies have shown efficacy of AAV5-miHTT in the lentivirally-derived HD rat model and in the humanised HD mouse model. In both models, AAV5-miHTT delivery resulted in a reduction of the disease-related HTT protein which was associated with a delay of neurodegeneration and in reduction of mtHTT aggregates. Furthermore, the miHTT processing, safety and off-target potential are being determined by next generation sequencing (NGS) on RNA isolated from murine striata and cortices to support the selection of the therapeutic candidate for clinical development. These preclinical results suggest that AAV5-miHTT may provide important therapeutic benefit for the HD patients and will allow for long-term HTT suppression upon a single vector administration.